DOM JEURAT RITUAL AMONG THE PEOPLE OF LUENG IE IN KRUENG BARONA JAYA DISTRICT, ACEH BESAR REGENCY - Rivatul Aina; Nuraini A Manan (Indonesian Journal of Islamic History and Culture, 2022)
Dom Jeurat ritual is a tradition performed by some Muslims in various regions in Indonesia, especially in Aceh. People finish reading the Qur'an by the grave for three days and three nights or seven days and seven nights according to the request of the family. This study aims to determine the process of the dom jeurat ritual, the response of religious leaders, the community, and the views of four imams of the school of thought regarding the ritual. In this study the authors used qualitative research methods. Collecting data in this study also through observation, interviews and documentation. The results showed that the dom jeurat ritual had been traditionally performed by earlier generations of the people of Lueng Ie Village since the time of their ancestors. However, no clear evidence was found by whom and in what year this activity was originally performed. There has never been strong evidence or written records regarding dom jeurat activities. From the views of the four imams of the sect and the responses of Tengku (local ulama) and the community in Lueng Ie Village regarding the activity of reciting the Koran at the cemetery, some allow it and some consider it is makruh. The main debate is not about whether or not to recite the Koran in the cemetery, but whether or not the prayers are religiously acceptable and could reach the corpse in the grave.